Multicentric T-cell Lymphoma with Metastases in the CNS of an Equine - Rosa Venancio, Fabiano; Santos Alberti, Taina; Valeska Scheid, Haide; Martins Engelmann, Thais; Viégas Sallis, Eliza Simone; Schild, Ana Lucia (Acta Scientiae Veterinariae, 2024)
Background: Lymphomas are neoplasms of hematopoietic origin and can affect all domestic species. In horses, the pathogenesis of lymphoma is still controversial, but it is known that it is not related to viral infections as it occurs in cattle and cats. The overall incidence of lymphomas in the world’s equine population is between 1.3% and 2.8% of all neoplasms in this species, and cases of primary lymphomas or metastases to the central nervous system (CNS) are rare. The objectives of this paper were to report one case of multicentric lymphoma with metastasis in the CNS of an equine and to describe the macroscopic, histological and immunohistochemical characteristics of this neoplasm. Case: A Crioulo male equine with a history of respiratory distress and locomotor disorders was necropsied. Macroscopically, firm whitish cutaneous nodules 3-10 cm in diameter were observed. Also, the mesenteric lymph nodes were increased in size, and yellowish nodules 0.2-0.7 cm in diameter were observed in the left adrenal gland. Nodules similar to the skin nodules were observed in the lung and in the thoracic cavity. Between the 6th and 7th thoracic vertebrae, there was a rounded, white and firm nodule. Fragments of all nodules, organs and the CNS were collected and fixed in 10% buffered formalin. Subsequently, these tissues were routinely processed, and selected sections were submitted to immunohistochemistry (IHC) using CD3 and CD79α antibodies. Histologically, in all sections, there was proliferation of pleomorphic lymphocytes with scarce cytoplasm, large, vacuolated nuclei and evident nucleoli, and 2 to 4 mitotic figures per higher magnification field. A thin fibrovascular stroma supported neoplastic cells that were arranged in cords or mantle. In the CNS, neoplastic cells were located both inside and around vessels forming cuffs. There were tumor cells inside blood vessels in the skin nodules. On IHC, the samples showed intense positive immunostaining for CD3 and were negative for CD79α. Discussion: In the literature, there are few cases of neoplasms affecting the CNS of horses, but among the reported cases, the most prevalent are lymphomas. In the majority of cases of equine lymphomas, several organs have had lesions, and consequently, clinical signs are related to the affected systems and organs. Multicentric lymphomas are the most frequently diagnosed in horses, and it has been mentioned that the most frequent histogenesis is malignant T-cell–rich large B-cell lymphoma, followed by peripheral T-cell lymphomas. Neoplasia in the equine CNS is rare, and when it occurs, it is often associated with multicentric lymphomas. Cases of solitary malignant lymphomas in the equine CNS are rare. Lymphomas with lesions in different regions of the CNS and peripheral nerves have been mentioned in horses and are associated with B and T lymphocytes, with a predominance of B lymphocytes. The perivascular localization of neoplastic cells in the nervous system has been reported, as in the present case, reinforcing the hypothesis that these are metastases and not a primary neoplastic site. This paper led to the conclusion that multicentric lymphomas should be considered in the differential diagnosis of other diseases, including neurological diseases. The importance of careful histological analysis even in organs that do not present macroscopic lesions is also concluded. The location of tumor cells within and around vessels in different regions of the CNS demonstrated that, in this case, there was metastasis to this organ. Keywords: equine, immunohistochemistry, IHQ, lymphoma, central nervous system, CNS. Título: Linfoma multicêntrico de células T com metástases no SNC em um Equino Descritores: equino, imunohistoquímica, IHQ, linfoma, sistema nervoso central, SNC.